2010
DOI: 10.1117/12.846769
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of double-patterning techniques for advanced logic nodes

Abstract: The development of Double-Patterning (DP) techniques continues to push forward aiming to extend the immersion based lithography below 36 nm half pitch. There are widespread efforts to make DP viable for further scaling of semiconductor devices. We have developed Develop/Etch/Develop/Etch (DE2) and Double-Expose-Track-Optimized (DETO) techniques for producing pitch-split patterns capable of supporting semiconductor devices for the 16 nm and 11 nm nodes. The IBM Alliance has established a DETO baseline, in colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…( ) Figure 17 Litho Freeze Litho overlay on resolution results and spaces CDU using a process as described in [2].…”
Section: Litho Freeze Lithomentioning
confidence: 99%
See 1 more Smart Citation
“…( ) Figure 17 Litho Freeze Litho overlay on resolution results and spaces CDU using a process as described in [2].…”
Section: Litho Freeze Lithomentioning
confidence: 99%
“…The second relevant application is a Litho Freeze Litho (LFL) application using a thermal cure process as described in [2] . The CDU of the spaces is determined by the overlay between the 2 exposures and the CDU of the lines following equation 1 [10] .…”
Section: Litho Freeze Lithomentioning
confidence: 99%
“…Over the past years, EUV lithography has been actively researched and developed as the next-generation lithography (NGL) solution although its readiness for high volume manufacturing (HVM) has been long-awaited and still unclear 1,2 . Double patterning techniques, such as litho-litho-etch (LLE) 3,4 , litho-etch-litho-etch (LELE) 5,6 , and self-aligned double patterning (SADP) 7,8 have been developed to extend the ultimate resolution k 1 factor of 193 nm immersion lithography. However, the need for device scaling in 14 nm and beyond technology nodes necessitates the implementation of more aggressive multiple patterning techniques 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…There have been many discussions [1][2][3][4][5] on wafer process and layout decomposition for two typical double patterning approaches: Litho-Etch-Litho-Etch (LELE) and Self-Aligned Double Patterning with spacer lithography (SADP). It has been shown that there are additional process constraints due to the double patterning nature of DPT.…”
Section: Introductionmentioning
confidence: 99%